Pendampingan Pengembangan AEA (Arabic English Area) dalam Menghadapi Era Revolusi Industri 4.0 di Pondok Pesantren Darussalam Dungmas Kedungrejo Sumberejo Bojonegoro - Sutopo Sutopo; Musbikhin Musbikhin; Muhyidin Muhyidin; Ahmad Sobihul Hadi; Aditia Putra Alandi (KERIS : Journal of Community Engagement, 2022)
This devotion aims to obtain results regarding the Development of Arabic and English at Pondok Pesantren Darussalam in the Era of the Industrial Revolution 4.0. This devotion is expected to be used as a form of attention to the importance of Arabic and English in the era of the industrial revolution 4.0. And hopefully this devotion can make santri more enthusiastic in learning Arabic and English in the future. In this devotion use the ABCD strategy. This strategy includes five stages: inculturation, discovery, design, define and reflection. The results of the devotion showed that the development of Arabic and English in Darussalam Dungmas boarding school, kedungrejo, Sumberejo, Bojonegoro using ABCD strategy was very effective and efficient. Where the concept of implementation in the service of Arabic and English development by using ABCD strategy has a good response, especially from caregivers, administrators and also draussalam boarding school students to support their own boarding schools and students in the era of the industrial revolution 4.0. However, in devotion will not be separated from the inhibitory factors that become obstacles to the language skills of the students of Darussalam Sumberejo Bojonegoro boarding school.